The role of effective albumin in chronic liver disease - LIN Jun, LI Zepeng, YU Junying (Jichu yixue yu linchuang)
Effective albumin refers to serum albumin with intact structure and function. In the course of chronic liver disease, some serum albumin loses its functional integrity through different post-translational modifications such as oxidation and glycosylation. Level of effective albumin is lower in patients with decompensated cirrhosis and is significantly correlated with patient survival, underscoring that they are more sensitive than total serum albumin in reflecting the actual state of liver function. In addition, effective albumin not only serves as a predictor, but also plays a key role in the treatment of chronic liver disease by improving albumin preparations and developing new therapeutics.